THERMAL SIZE EFFECTS IN CONTACT METAL SEMICONDUCTOR - Gulomov Gafurjon; Kudiratulla Bekbaevich; Umarov Kudiratulla Bekbaevich (International Journal on Orange Technologies, 2020)
The heating of electrons and phonons, as well as thermal size effects in the Schottky barrier, are investigated. The dependence of the electron and phonon temperature is analyzed depending on the thermal boundary conditions and the sample size. It was found that in thin (ka << 1) diodes at the contacts, the electron temperature is much higher than the phonon temperature. When the condition of ideal heat transfer is satisfied in an ohmic contact, the temperatures of electrons and phonons coincide with the ambient temperature. In massive (ka >> 1) diodes in the volume, the temperatures of electrons and phonons coincide, and in an ohmic contact, the temperatures coincide with the ambient temperature.